Social condensation in the Metropole: locating the first New Left. Issue 3 (3rd April 2017) - Beech, Nick
Abstract : From 1956 to 1962 the 'first' New Left in Britain made radical critical interventions in the politics and culture of the welfare state. Typically, the work of the leading intellectuals in this movement—including Stuart Hall, Raphael Samuel, Edward Thompson and Raymond Williams—has been understood as part of an intellectual history: either of Marxism or cultural studies. I argue that it is better to understand the New Left in Britain as a practical political and cultural project, intervening in and productive of specific kinds of spatial environment. To develop this argument, two examples of such spaces are examined: The Partisan Coffee House, established in 1959 by Raphael Samuel as an 'anti-expresso bar' and the Secondary Modern school where Stuart Hall worked as a supply teacher. The former site is understood as a 'milieu', the latter as a 'concentration' in the contested metropole of London. Throughout, a question over the determinate relationship of art to society is raised, with implications for political analysis and action.